Pediatric nasoseptal flap reconstruction for suprasellar approaches. (28th May 2015) - Ghosh, Ankona; Hatten, Kyle; Learned, Kim O.; Rizzi, Mark D.; Lee, John Y.; Storm, Phillip B.; Palmer, James N.; Adappa, Nithin D.
<x xml:space="preserve">Abstract</x> Objectives/Hypothesis To determine the pediatric age groups viable for nasoseptal flap (NSF) reconstruction of endoscopic endonasal approaches (EEA) to intracranial pathology of suprasella neoplasms. Study Design Retrospective cohort study. Methods Retrospective review of 16 pediatric patients who underwent EEA with NSF reconstruction for a suprasellar defect from 2012 to 2014. Radioanatomic analysis was utilized to assess feasibility of NSF reconstruction of suprasellar neoplasms approached via EEA. Computed tomography (CT) measurements for defect size and potential flap coverage were measured by preoperative maxillofacial CT. Radiographic measurements and surgical outcomes were compared to determine if flap size would be sufficient to cover said defects in two pediatric age groups: those >10 years of age (mean age 14 years) and those <10 years (mean age 6 years). Results Of all patients encountered in this cohort, one postoperative cerebrospinal fluid leak was identified in the >10 years of age population, and this was not due to insufficient flap coverage. Average potential flap length and width are sufficient to cover average suprasellar defect length and width in both age groups (P < .05 in all age groups). Conclusions Patient selection is critical for successful pediatric EEA. Preoperative radiographic assessment of NSF feasibility is a critical to ensure adequate flap coverage for suprasellar defects. NSF appears to provide a sufficient and reliable coverage option in reconstruction of suprasellar defects in pediatric patients. Level of Evidence 4. Laryngoscope, 125:2451–2456, 2015